Cultured cells as a model for amphibian metamorphosis. - Kanamori, A (1993)
Gene expression screens have been applied to a cultured cell line of Xenopus laevis, XL-177, to isolate genes that are up- and down-regulated in the first 8 h after thyroid hormone (TH) induction. At least 14 up-regulated genes were isolated from TH-induced cells grown in the presence or absence of cycloheximide, an inhibitor of protein synthesis. These genes respond directly to TH as demonstrated by the resistance of up-regulation to protein synthesis inhibition in the cultured cells or in tadpoles. Kinetics of mRNA accumulation after TH induction is similar for these genes, including those that are superinduced by cycloheximide. Their mRNAs start to be up-regulated several hours after TH treatment and reach maximum levels between 8 and 16 h. These genes show up-regulation in one or more tadpole organs in response to exogenous TH. Only a few minimally down-regulated genes were identified. Fourteen of the 20 genes that were found to be up-regulated by TH in tadpole tail are also up-regulated in XL-177 cells. Their up-regulation falls into the same two kinetic patterns in the cultured cells as it does in tadpole tail. Another cell line of X. laevis, XLA, is greatly reduced in its ability to up-regulate the same genes isolated from XL-177 cells and tadpole tails in response to TH. Thus these cell lines make up a model system to examine the interactions of gene expression triggered by TH during amphibian metamorphosis.